PENERAPAN MODEL EXPERIENTIAL LEARNING PADA MATA PELAJARAN PRAKARYA DAN KEWIRAUSAHAAN UNTUK MENINGKATKAN SKILLS BERWIRAUSAHA SISWA - RISKI AYU ARNILA (Journal Ilmiah Rinjani : Media Informasi Ilmiah Universitas Gunung Rinjani, 2020)
The purpose of this research is to improve the student’s entrepreneurial skills by implementingexperiential learning on entrepreneurial learning. This research is an action research. Thesubject of this research was student of X grade of hotelier accommodation 2 program of SMKNegeri 7 Surakarta which is consisting of 32 students. The data of this research were collectedby using observation, interview, document analysis and questionnaire methods. They wereanalyzed by using mixed methods. The type of mixed methods analysis was convergen parallelmixed methods. The results of this research showed that the implementation of experientiallearning models on entrepreneurial learning increase the student’s entrepreneurial skills. Itcharacterized by an increasing in the average value of student’s entrepreneurial skills in SMKNegeri 7 Surakarta where the value of student’s entrepreneurial skills is 63,016 before treatmentbecome 80,018 after treatment in the first cycle anda become 81,232 in the second cycle. In thefirst cycle 87,5% student achived the value above the passing grade score. Then in the secondcycle 90,63% student achived the value above the passing grade score. Raising the student’sentrepreneurial skills also showed by various change in the student’s behavior and skills fromvarious aspects, they are conceptual skill, leadership skill, management skill, technical skill,social skill, selling skill, dan creative.Kata Kunci: Experiential Learning, Entrepreneurial Learning, Entrepreneurial Skills.